2018
DOI: 10.4103/ijt.ijt_62_18
|View full text |Cite
|
Sign up to set email alerts
|

A comment on JAK inhibitors for treatment of alopecia areata

Abstract: A meta-analysis of published trials on the treatment of alopecia areata (AA) came to the conclusion that most have been reported poorly and so small that any important clinical benefits are inconclusive, and considering the possibility of spontaneous remission, especially for those in the early stages of the disease, the options of not being treated or depending on individual preference, and of wearing a wig may be alternative ways of dealing with the condition. And yet, from clinical practice, we know that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Many case reports and limited clinical studies demonstrated impressive therapeutic effects of JAK inhibitors in patients with AA. 57,115,116 In current practice various JAK/signal transducer and activator of transcription (STAT) inhibitors are probably the most effective new pharmacologic intervention strategies currently under development (Fig 1, A). However, concerns still exist regarding unknown long-term side effects with these medications.…”
Section: Novel Therapeutic Intervention Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many case reports and limited clinical studies demonstrated impressive therapeutic effects of JAK inhibitors in patients with AA. 57,115,116 In current practice various JAK/signal transducer and activator of transcription (STAT) inhibitors are probably the most effective new pharmacologic intervention strategies currently under development (Fig 1, A). However, concerns still exist regarding unknown long-term side effects with these medications.…”
Section: Novel Therapeutic Intervention Strategiesmentioning
confidence: 99%
“…Given their promise as effective novel AA therapeutics, 58,59,115 it is perfectly understandable that most investigators in both academia and industry currently seem to focus on JAK/STAT inhibitors. These inhibitors block signaling through a broad range of receptors that use the JAK/STAT pathway and do not really provide new insight into the pathogenesis of AA.…”
Section: Final Perspectivesmentioning
confidence: 99%
“…Although AA has been described as a benign, self-limiting condition with most cases resulting in spontaneous regrowth, this regrowth may take place over a period of several months to years, with approximately 66% of patients showing complete regrowth of hair within 5 years. 4 However, relapse is common in AA, and studies have reported that in patients observed over a period of 10–20 years that the overall incidence rate of relapses ranges from 85–100%, with 100% relapse being observed in patients over a 20-year period. 4 For patients who progress to the more severe forms of AT and AU, 75% will remain with AT and 34% of adults (44% children) would experience periods of hair growth with AU.…”
Section: Introduction/ Backgroundmentioning
confidence: 99%
“… 4 However, relapse is common in AA, and studies have reported that in patients observed over a period of 10–20 years that the overall incidence rate of relapses ranges from 85–100%, with 100% relapse being observed in patients over a 20-year period. 4 For patients who progress to the more severe forms of AT and AU, 75% will remain with AT and 34% of adults (44% children) would experience periods of hair growth with AU. 4 From this, it is clear that patients may experience many difficulties while dealing with this disease.…”
Section: Introduction/ Backgroundmentioning
confidence: 99%
See 1 more Smart Citation